Reinterpreting agencies in UK central government: on meaning, motive and policymaking - Elston, Thomas (2014)
This thesis is a qualitative and interpretive exploration of continuity and change in the role of executive agencies in UK central government. Its three objectives are: (i) to test the longevity of the semi-autonomous agency model first introduced by Conservative governments after 1988; (ii) to explore the department-agency task division in the policymaking processes supposedly fragmented by this ‘agencification’; and (iii) to evaluate the paradigmatic testament of contemporary agency policy and practice in Whitehall. The thesis builds from an extended case study conducted during the 2010 Coalition Government in the Ministry of Justice and three of its agencies – the National Offender Management Service, HM Courts and Tribunals Service, and the Office of the Public Guardian. Social constructivist meta-theory and the application of narrative and discourse analysis together make for an account of interpretive transformation that is theorised by discursive institutionalism.